Charles Sanders Peirce Semiotic Analysis of Documentary Film Dirty Vote - Taufani, Maurina; Bajari, Atwar; Supriadi, Dandi (Journal La Sociale, 2025)
The documentary entitled "Dirty Vote" which was delivered directly by three constitutional law experts and aired during the quiet period of the 2024 presidential election has been watched 9.6 million times on the youtube channel of the Indonesian Center for Law and Policy Studies. This film attracted the attention of the Indonesian people at that time, because this film discussed the analysis of fraud by the country's political actors during the 2024 presidential campaign. However, the movie not only highlighted the problems that occurred during the election process, but also provided space to explore possible solutions to overcome these challenges. Therefore, this research aims to look at the reality, representation, and ideology as well as the signs used by the film director in packaging this movie. This research uses Charles Sanders Peirce's semiotic analysis that puts forward Reality, Representation, and Ideology in each scene analyzed. The results showed that researchers found three different scenes that were explained in detail with specific signs. Starting from the opening scene and the introduction of the main character, political campaigns and political scandals. All signs contained in this movie have their own meaning.